2018
DOI: 10.1002/jso.25198
|View full text |Cite
|
Sign up to set email alerts
|

Modern techniques and alternative flaps in microsurgical breast reconstruction

Abstract: Breast reconstruction with autologous tissue has become an essential part of the breast cancer patient care algorithm, with the abdomen being the most common tissue donor site. However, within this field, the technology and surgical techniques available to the reconstructive breast surgeon have evolved over time. This review aims to summarize the literature surrounding current techniques in microsurgical breast reconstruction including the use of alternative, nonabdominal flaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 67 publications
(85 reference statements)
0
16
0
Order By: Relevance
“…Th e statistical analysis revealed that the use of classical breast reconstruction techniques 17 , using tissue expanders and silicone implants, is an eff ective measure for the recovery of these patients. Whether we are talking about immediate implant reconstruction or two-step reconstruction after the initial tissue expansion, the duration of hospitalization is reduced when using prosthetic materials, the results are predictable and off er a high degree of patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Th e statistical analysis revealed that the use of classical breast reconstruction techniques 17 , using tissue expanders and silicone implants, is an eff ective measure for the recovery of these patients. Whether we are talking about immediate implant reconstruction or two-step reconstruction after the initial tissue expansion, the duration of hospitalization is reduced when using prosthetic materials, the results are predictable and off er a high degree of patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The patient is subject to radiation to obtain CTA imaging. While MRA does not involve ionizing radiation, this technique is more costly and may not be widely accessible or available to all patients (7).…”
Section: Computed Topographic Angiography (Cta) or Magnetic Resonance Angiography (Mra)mentioning
confidence: 99%
“…Based on this information, the surgeon can expertly design flaps based on preoperatively determined perforators that limit patient morbidity (i.e., those with a shorter intramuscular or no intramuscular course) and approach key perforators quickly to improve efficiency and decision-making intraoperatively (Figure 1). Additional benefits of preoperative imaging include volumetric analysis of donor and recipient sites (Figure 2) and being an adjunct tool in the training of residents and fellows (7,16,17). With regards to autologous breast reconstruction, imaging provides the surgeon with a more accurate assessment of available donor site tissue to reconstruct the breast following mastectomy, potentially alerting the clinician to the need for additional volume in the form of extended or additional flaps (18,19).…”
Section: Computed Topographic Angiography (Cta) or Magnetic Resonance Angiography (Mra)mentioning
confidence: 99%
See 1 more Smart Citation
“…These include the lumbar artery perforator, profunda artery perforator, transverse gracilis myocutaneous, superior gluteal artery perforator, inferior gluteal artery perforator, or lateral thigh perforator flaps. 39 With the appropriate patient and flap donor sites selected, the challenge then becomes flap arrangement for inset and anastomotic technique. Recipient site vessel options for free flap reconstruction include the internal mammary vessels (either antegrade or retrograde), IMA perforators, intercostal perfora-tors, circumflex scapular, or the thoracodorsal vessels.…”
Section: Videomentioning
confidence: 99%